A Qualitative Study on The Function of Information and Communication Technology Utilization in Teaching Students with Intellectual Disabilities: Implications for Techniques of Teaching/Job Coaching - Maebara, Kazuaki; Yamaguchi, Asuka; Suzuki, Toru; Imai, Aya (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Recently, the use of Information and Communication Technology (ICT) in education has been promoted in Japan. However, teachers do not yet fully understand using ICT for persons with intellectual disabilities. Objective: This study clarifies the support functions of ICT as perceived by teachers involved in special needs education (support for students with intellectual disabilities). Methods: We conducted in-depth interviews with five teachers involved in special-needs education. We qualitatively analyzed the interview data obtained using content analysis. Results: From the interviews, 53 ICT-utilization episodes were obtained. These episodes were categorized into 13 categories of utilization and seven aspects of support: understanding, communication, behavior, meta-cognition, environment, memory, and opportunities. Conclusion: ICT is a beneficial tool to compensate for intellectual disabilities and help students with intellectual disabilities learn better. We believe that teachers can better assist students with intellectual disabilities by successfully matching individual needs with the ICT features. The results obtained in this study will be helpful while considering support for persons with intellectual disabilities, not only in education but also in vocational training, employment support, and telework support for persons with intellectual disabilities.